VHF band spaceborne element rotation angle controlled phased antenna array for SAT‐AIS application. Issue 6 (19th February 2020) - Xue, Kai; Liao, Shaowei; Xue, Quan; Ding, Liqin; Wang, Yang; Guo, Qing
Abstract: A novel very‐high frequency (VHF) band spaceborne phased antenna array for satellite‐automatic identification system/VHF data exchange (SAT‐AIS/VDE) applications operating at 159 MHz is proposed in this letter. Element phase shifting is achieved by controlling each element mechanical rotation angle rather than the phase shifter behind each element. Thanks to the new working scheme, the proposed array shows several advantages over its former counterpart, including low cost, high power capacity, and broad phase‐shifting bandwidth. This letter explains the basic principle, and presents a preliminary study on element rotation angle controlled phased antenna array technology, and an eight‐element‐array which is implemented on solar panel supporting plate is designed to validate the concept.